Picroside II attenuates ischemia/reperfusion testicular injury by alleviating oxidative stress and apoptosis through reducing nitric oxide synthesis - Li,Yanze (2019)
Abstract Purpose: To investigate the effect of Picroside II on testicular ischemia and reperfusion (l/R) injury and the underlying mechanism. Methods: Sprague-Dawley rats were randomly divided into 4 groups: sham operated group (Sham), Sham with Picroside II treatment group (Sham+ Pic II), l/R group (l/R) and l/R with Picroside II treatment group (I/R+ Pic II). l/R model was established by rotating the left testis 720° in a clock-wise direction for 4 hours. The histopathologic and spermatogenetic evaluation was performed. The apoptosis changes and the levels of HO-1 (heme oxygenase-1), MPO (myeloperoxidase), NOX (NADPH oxidase), SOD (superoxide dismutase), XO (xanthine oxidase) and NOS (nitric oxide synthase) were measured. Results: The seminiferous tubules were damaged in l/R rats, but Picroside II alleviated the changes induced by l/R. The increased level of apoptosis was decreased by Picroside II (P=0.01, 9.05±0.35 vs. 4.85±0.25). The activities of HO-1, MPO, NOX, XO and MDA content were increased and the SOD activity was decreased in l/R (P<0.05) and could be reversed by Picroside II (P=0.03, 405.5±7.5 vs. 304±17U/mgprot; P=0.02, 0.99±0.05 vs. 0.52±0.04 mgprot; P=0.01, 260+7 vs. 189±2 mgprot; P=0.04, 10.95+0.55 vs. 8.75+0.35 U/mgprot; P=0.045, 6.8+0.7 vs. 3.75+0.35 mgprot; P=0.04, 44.5+3.5 vs. 57.5+3.5 mgprot). Western blot showed that the expression of iNOS, nNOS and eNOS were increased in l/R (P<0.05); however, they were decreased after Picroside II treatment (P<0.05). Conclusion: Picroside II attenuated testicular I/R injury in rats mainly through suppressing apoptosis and oxidative stress through reduction of nitric oxide synthesis.